(untitled) (Biological Sciences - PJSIR, 2022)
EtOH five times, such that the last extract obtained, was almost colourless. All EtOH extracts were concentrated under reduced pressure to a brownish gummy mass. This gummy extract was acidified with 10% HCl (Merck) and extracted with CHC13 (Merck) to remove non-alkaloidal compounds. The acidic aqueous fraction was then basified with NH3 and extracted thoroughly with CHCI3.